Improving Problem-Solving Skills Through the Discovery Learning Model Assisted by Concrete Objects - Umiyati, Umiyati; Kartono, Kartono; Yumiati , Yumiati (Edumaspul: Jurnal Pendidikan, 2026)
Based on the research findings and discussion, it can be concluded that the implementation of the Discovery Learning model assisted by concrete objects enhances students’ mathematical problem-solving skills. This is evidenced by the increase in students’ average scores from the pretest to the posttest, a finding further supported by the N-Gain analysis. Students taught using the Discovery Learning model with concrete objects demonstrated superior mathematical problem-solving skills compared to those taught using conventional methods. This was confirmed by hypothesis testing using an Independent Sample t-test, which revealed a significant difference between the experimental and control classes. The use of the Discovery Learning model with concrete objects enables students to engage actively in the learning process, thereby helping them grasp mathematical concepts more meaningfully and improving their mathematical problem solving abilities.